Sibling Jealousy and Temperament: The Mediating Effect of Emotion Regulation in China During COVID-19 Pandemic - Qian, Guoying; Li, Ruonan; Yang, Wanqi; Li, Ranran; Tian, Li; Dou, Gang (Frontiers in Psychiatry, 2021)
This study aimed to examine first-born children’s sibling jealousy and explore the relationships among first-born children’s sibling jealousy, temperament, and emotion regulation. A sample of 304 two-child families from China participated in the study; the first-born children were aged between 1.17 and 7 years. The results indicated the following: (1) the older the first-born children and the greater the age difference between siblings, the lower the sibling jealousy. (2) Difficult temperament of first-born children could predict sibling jealousy significantly and positively, and emotion regulation could predict sibling jealousy negatively. (3) There was a partially mediating effect of emotion regulation between temperament and sibling jealousy. Compared with intermediate temperament, first-born children with difficult temperament had weaker emotion regulation and higher sibling jealousy. Overall, findings have important implications for psychological interventions for families of first-born children with difficult temperament.